Biallelic variants in the UTRN gene cause a novel form of multiple congenital arthrogryposis - Melnik, Evgeniya; Akimova, Daria; Markova, Tatiana; Tatarskiy, Eugene; Tvorogova, Anna; Zabnenkova, Viktoria; Kenis, Vladimir; Agranovich, Olga; Skoblov, Mikhail; Dadali, Elena (Frontiers in Genetics, 2025)
Arthrogryposis multiplex congenita (AMC) is a large group of congenital conditions characterized by joint contractures affecting two or more body areas. A part of AMC type is caused by heterozygous pathogenic variants in genes encoding sarcomeric components of skeletal muscle fibers. Here we report a 7-year-old boy with a phenotype including AMC with dysmorphic facial features, short stature, congenital malformations of brain, colon and lacrimal canal. Trio whole-genome sequencing identified compound heterozygosity in the UTRN gene, consisting of a splicing variant in intron 57 (c.8434 + 1G>A) and a large heterozygous deletion spanning exons 3–51 (NM_007124.3). It is known that utrophin, the product of the UTRN gene, is an autosomal homologue and a fetal form of a protein of skeletal muscles - dystrophin. The presence of multiple malformations in the patient’s phenotype is consistent with ubiquitous expression of utrophin in the embryonic period. The RNA-seq analysis revealed that the splicing variant introduces a premature termination codon, which is predicted to result in a truncated protein shorter by 615 amino acids (p.Val2786Argfs*34), and the deletion leads to transcription of a shortened RNA isoform. We suggest that these variants are hypomorphic and partially retain protein function, which explains the clinical picture in the patient. In aggregate, our findings provide evidence that rare biallelic recessive variants in UTRN cause a novel autosomal recessive multiple congenital arthrogryposis.